IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA BERBASIS KEARIFAN LOKAL TRADISI PETIK LAUT - Rohenah; Imam Syafi'i; Saiful Islam (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study aims to analyze the implementation of the Project for Strengthening the Pancasila Student Profile (P5) based on the local wisdom of the Petik Laut Tradition at SMKN 1 Kraksaan Probolinggo. This research employs a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews, and documentation. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which consists of data reduction, data display, and conclusion drawing. Data validity was ensured through source and method triangulation. The findings reveal that the implementation of the P5 program based on the Petik Laut Tradition is carried out through three systematic stages: planning, implementation, and evaluation. The Petik Laut Tradition is utilized as a contextual learning resource containing spiritual, social, and ecological values, thereby creating meaningful learning experiences. This implementation is effective in internalizing the six dimensions of the Pancasila Student Profile, namely faith and devotion to God Almighty and noble character, mutual cooperation, global diversity, independence, critical thinking, and creativity. The learning process also enhances students’ active participation through field observations, interviews, documentation, and project-based product creation. In addition, the study finds that the teacher’s role as a facilitator, community involvement, and school support are the main supporting factors for successful implementation. However, several challenges were identified, including limited implementation time, insufficient facilities and infrastructure, funding constraints, and differences in students’ understanding of cultural values. Overall, the implementation of P5 based on the Petik Laut Tradition strengthens students’ character while also preserving local culture within the context of 21st-century education.